Formadores de professores no ensino superior: olhares para trajetórias e ações formativas - Souza, Cirlei Evangelista Silva (2011)
The main objective of this study was to put through analysis the formative path of the teachertrainers of Universidade Federal de Uberlândia (UFU), trying to discuss the articulation between the formation and the formative action of these professionals. From a qualitativequantitative approach, the research was a case study and it was based on the historical-cultural psychology. The subjects of this work were teachers from UFU that teach on twenty-three degree courses, lecturing on Núcleo de Formação Pedagógica: Didática; Estágio Supervisionado; Metodologia e Prática de Ensino; Psicologia da Educação; Política e Gestão da Educação and Projeto Integrado de Prática Educativa (Pipe). During the construction of this work, the research instruments were question sheets, pre-formulated interviews, classes observation and data base analysis, that allowed tracing a profile and the formative path of teacher-trainers of UFU, pointing aspects of their personal, academic and professional background; and to turn possible a direct contact with those teachers on their field of action, acknowledging the state that s being investigated and the relations that the teachers make within this environment while showing their pedagogical practices. The outcomes shown that: 1) most of the teacher-trainers of UFU are, on its majority, females, with minimal doctor degree and also have a good professional experience on the education field; 2) their formative path prints signifying marks, that defines ones personality and professional experience; 3) there s an ongoing reproductive circle of a process that comes from the construction of the future teacher and goes to the professional life, indicating a strong relation between the conceptions and the formative practices and the conceptions and the teacher-trainers educative practices. So, these future-teachers became teachers and gathered different meanings to their experiences, it showed us that their formation and their pedagogical actions are intrinsic related to their background on the most different social-historical contexts. The results are important tools that can help us thinking of a collective construction project of continuous formation to the teacher-trainers. That would solve the need to create a collective construction inside the institution, that, the teachers could do their professional development and socialization, so that the action-formation unity could walk together with the transformation basis.